The FLOTAC basic technique as a new extraction method for root-knot nematodes (Meloidogyne spp.) from soil and roots - Troccoli, Alberto; d’Errico, Giada; D’Addabbo, Trifone; Sasanelli, Nicola; Bosco, Antonio; Maurelli, Maria P.; Rinaldi, Laura; Cringoli, Giuseppe (Frontiers in Parasitology, 2022)
FLOTAC Techniques have been widely acknowledged as an effective method for the extraction of human and animal parasites. The present study is the first application of FLOTAC basic technique (FBT) for the extraction of phytoparasitic nematodes from soil and infested plant roots. Eggs and second stage juveniles (J2) of the root-knot nematode Meloidogyne incognita were extracted from infested soil and tomato roots either by FBT and conventional nematode extraction methods, such as flotation-centrifugation and root maceration techniques, respectively. The number of M. incognita J2 and eggs extracted from soil by FBT was always significantly higher compared to the extraction with the flotation-centrifugation method, averaging 277 vs 35 eggs and J2 mL-1 soil. Conversely, no significant differences were observed between FBT and the root maceration technique in the extraction of eggs and J2 from tomato roots. Results demontrated that FBT can be highly effective also for the extraction of phytoparasitic nematodes. Due to its accuracy and sensitivity, FBT seems particularly suitable for nematode surveys in wide geographical areas, where an accurate and rapid detection of present phytoparasitic nematofauna is required.